2021
DOI: 10.4239/wjd.v12.i11.1856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycemic control on markers of subclinical atherosclerosis in patients with type 2 diabetes mellitus: A review

Abstract: Cardiovascular disease is the predominant cause of death in type 2 diabetes mellitus (T2DM). Evidence suggests a strong association between duration and degree of hyperglycemia and vascular disease. However, large trials failed to show cardiovascular benefit after intensive glycemic control, especially in patients with longer diabetes duration. Atherosclerosis is a chronic and progressive disease, with a long asymptomatic phase. Subclinical atherosclerosis, which is impaired in T2DM, includes impaired vasodila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 119 publications
0
7
0
2
Order By: Relevance
“…Another important comment is related to the duration of diabetes, with a mean of 4.9 years in all diabetic patients and significantly higher in patients with microangiopathy. This is particularly relevant because it has been previously demonstrated that a diabetes duration of more than 5 years can accelerate stiffness of the arteries and this can have an impact in the results obtained, because it was not included in the adjustment made in multivariable analysis 5 . In addition, nonlinearity of the wall's stress–strain relationship is more pronounced at high pressure, making ES more dependent on systolic pressure than BS on diastolic pressure and results should also be adjusted to consider blood pressure, despite similar mean values in both groups 2 .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Another important comment is related to the duration of diabetes, with a mean of 4.9 years in all diabetic patients and significantly higher in patients with microangiopathy. This is particularly relevant because it has been previously demonstrated that a diabetes duration of more than 5 years can accelerate stiffness of the arteries and this can have an impact in the results obtained, because it was not included in the adjustment made in multivariable analysis 5 . In addition, nonlinearity of the wall's stress–strain relationship is more pronounced at high pressure, making ES more dependent on systolic pressure than BS on diastolic pressure and results should also be adjusted to consider blood pressure, despite similar mean values in both groups 2 .…”
mentioning
confidence: 99%
“…This is particularly relevant because it has been previously demonstrated that a diabetes duration of more than 5 years can accelerate stiffness of the arteries and this can have an impact in the results obtained, because it was not included in the adjustment made in multivariable analysis. 5 In addition, nonlinearity of the wall's stressstrain relationship is more pronounced at high pressure, making ES more dependent on systolic pressure than BS on diastolic pressure and results should also be adjusted to consider blood pressure, despite similar mean values in both groups. 2 Finally, it has been demonstrated previously that in patients without evident macrovascular involvement, higher insulin levels remain a significant predictor of PWV even after adjustment for other well established risk factors for atherosclerosis.…”
mentioning
confidence: 99%
See 3 more Smart Citations